2017
DOI: 10.1177/0972262917733157
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting International Reserves with Special Reference to India

Abstract: World international reserves holdings have accelerated sharply in recent times. Countries particularly developing ones are competitive enough to hoard these reserves and top 10 major holders are mostly from Asia. Interestingly India comes only ninth among them. Developing countries, particularly India, are in line to hoard foreign reserves and there are certain factors that affect international reserves holdings. This study analysed the impact of few macroeconomic factors on these reserves. Augmented Dickey Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Ume and Ndubuaku (2019) have also found a long-run relationship between the foreign reserve and the real exchange rate in Nigeria by using the ARDL bound test approach. Kashif et al (2017) have used the Johansen cointegration procedure to study the relationship among foreign exchange reserve, trade openness, and economic growth and revealed the long-run equilibrium relationship among the variables. The error correction mechanism has shown the negative relationship between trade openness and foreign exchange reserve, while the economic growth variable has exhibited a positive relationship with reserve.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Ume and Ndubuaku (2019) have also found a long-run relationship between the foreign reserve and the real exchange rate in Nigeria by using the ARDL bound test approach. Kashif et al (2017) have used the Johansen cointegration procedure to study the relationship among foreign exchange reserve, trade openness, and economic growth and revealed the long-run equilibrium relationship among the variables. The error correction mechanism has shown the negative relationship between trade openness and foreign exchange reserve, while the economic growth variable has exhibited a positive relationship with reserve.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foreign exchange reserve (FER) plays a pivotal role in reducing external debt risks and mitigating the adverse shocks of an unanticipated waning of capital inflow or capital flight (Yongzhong & Freeman, 2013). Usually, countries hold foreign exchange reserves to maintain exchange rate stability and safeguard other economic activities (Kashif, Sridharan, & Thiyagarajan, 2017). A sizeable foreign exchange reserve bolsters a country's competency to carry out various projects and aid to promote economic development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study uses the definition of IR as suggested by International Financial Statistics. IR include commodities such as gold, foreign currency deposits of the monetary authority, reserve position of the country with IMF and also SDRs (Kashif, Sridharan, & Thiyagarajan, 2017). Furthermore, gold is also excluded because it is negligible when calculated in comparison to the other components of IR.…”
Section: Data Descriptionmentioning
confidence: 99%